A Piece of Qualitative Study About Digital Natives. (1st May 2016) - Uygarer, Rahme; Uzunboylu, Huseyin; Ozdamli, Fezile
Abstract: This research is conducted to examine how the concepts of digital natives and digital immigrants are represented in the literature. Therefore, qualitative research methodology was preferred for the research. Data collection was done through literature review. Keywords such as digital natives and digital immigrants in education are used to search for details about digital natives and digital immigrants in education settings. Thus, literature review is analyzed to find common points in the researches. Findings show the importance of new technology and the usage of technology in education settings, and also how the digital natives learn within this age. To sum up therefore, it is proven that being a digital native and being a digital immigrant are two different things in an education setting. In recent studies however, issues such as being a digital native and being a digital immigrant are to be adopted as novelties and learnt within a multiplatform. Thus, learning platforms and techniques are constantly changing with respect to technological changes, and the students are also influenced, as their way of learning keeps changing.